2006
DOI: 10.1115/1.2349563
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Acoustic Resonance in a Staggered Tube Array

Abstract: Experimental laboratory research was performed to study the effect of test section width on the magnitude of acoustic resonance generated in a small pitch ratio staggered tube bank. Three different test section widths were studied: 505mm, 714mm, and 953mm. The results for acoustic resonance were compared to the tube bank data of Blevins and Bressler (1993, J. Sound Vib., 164(3), pp. 503–533), Ziada, Bolleter, and Chen (1984, ASME Symposium on Flow-Induced Vibrations, ASME, New York, Vol. 2, pp. 227–242); Ziada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…Additional tests were carried out using anti-resonance baffles 0.2 mm thick. Anti-resonance baffles are usually used within a tube bundle to avoid acoustic resonance by increasing the natural acoustic frequency [23,24]. The first modes of the natural frequencies were The test apparatus consisted of a rectangular duct, a ring blower, an orifice, a bell mouth, and two tube bundles.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Additional tests were carried out using anti-resonance baffles 0.2 mm thick. Anti-resonance baffles are usually used within a tube bundle to avoid acoustic resonance by increasing the natural acoustic frequency [23,24]. The first modes of the natural frequencies were The test apparatus consisted of a rectangular duct, a ring blower, an orifice, a bell mouth, and two tube bundles.…”
Section: Methodsmentioning
confidence: 99%
“…Acoustic resonance can occur when the vortex shedding frequency is close to the natural frequency of the transverse acoustic mode (f % f n ) [17][18][19][20][21][22][23][24][25][26][27][28], and the flow is prominently affected by the acoustic resonance [29,30]. Blevins and Bressler [18] found that acoustic resonance could cause the pressure drop that occurs through a tube bundle to increase significantly.…”
Section: Acoustic Resonance and Pressure Dropmentioning
confidence: 99%
See 1 more Smart Citation
“…They reported measurements of Strouhal number and acoustic noise and developed a correlation to predict the loudness of the acoustic noise based upon Mach number and pressure drop across the tube array. In a recent study, Feenstra et al (2006) showed that the test-section width affected the maximum sound pressures achieved at resonance and, in particular, that wider test-sections produced higher sound pressure levels in the first five acoustic modes than predicted by Blevins and Bressler (1993).…”
Section: Introductionmentioning
confidence: 95%
“…(Eisinger & Sullivan , 2007) considers strong acoustic resonance with acoustic pressure reading 165 dB for package boiler at near full load, suppression of resonance (lower frequency) through baffle covering with downstream section and the development of another resonance (higher frequency) in the unbaffled upstream section. (Feenstra et al, 2006) carried out experimental investigation of the effects of width of test section for measuring the acoustic resonance with a small pitch rates staggered tubes. The conclusion was that the maximum acoustic pressure versus input energy parameter of Blevins and Bressler is not a reliable preditor and it over predicts.…”
Section: Acoustic Resonancementioning
confidence: 99%